Assessment of soil fertility using the soil fertility index method on several land uses in Tutur District, Pasuruan Regency of East Java - Purnomo Edi Sasongko; Purwanto Purwanto; Widyatmani Sih Dewi; Ramdan Hidayat (Journal of Degraded and Mining Lands Management, 2022)
Changes in land use have an impact on the level of soil fertility. Soil management, such as land cover systems and the environment, are supporting factors. Assessment of soil fertility index using indicators of soil chemical properties such as organic C, availability of nutrients nitrogen (N), phosphorus (P), cation exchange capacity (CEC), and exchangeable cations (K, Ca, Mg, Na). The research was conducted in Tutur District, Pasuruan Regency, with a survey of 5 land uses, i.e., mixed crops, coffee plantations, apple plantations, vegetable fields, secondary forests, and conservation forests. Observations were made on elevation, slope, and vegetation. Parameters of physical properties measured were soil texture and aggregate stability. Observations of chemical properties included organic C, N, P, CEC, exchangeable cation (K, Ca, Mg, Na), and soil pH. Soil Fertility Index (SFI) data were analyzed using the Least Significant Difference method at a 5% level. The results showed the diversity of soil fertility levels obtained from the calculation of the soil fertility index. The soil fertility index value in 5 land uses in Tutur District ranged from 0.67 to 1.00. Coffee plantations had the highest SFI score of 1.00; this condition was supported by an organic C indicator of 6.21% and a CEC value of 39.12 cmol kg-1. Conservation forest is the land use with the lowest SFI value of 0.67. The value of CEC and cation exchange in conservation forests are factors that impact the low value of SFI.